Microparticles loaded gellan gum hydrogel matrices: engineering tissues for nucleus pulposus regeneration - Pereira, D. R. (2012)
The intervertebral disc central core is made by a gel-like tissue structure composed of more than 80% of water, Nucleus Pulposus (NP). Proteoglycans such as versican and especially aggrecan are the main constituents of the NP matrix as well as collagen type II. The purpose of this work is creating novel Gellan gum-based (GG) hydrogel formulations. GG microparticles (MPs) dispersed in a GG matrix are the novelty for finding application as NP substitute. The ongoing experiment comprises de GG functionalization through methacrylated groups addition. In order to optimize some properties of GG, the functionalization will allow us to improve the water solubility and photopolymerization in situ of the biomaterial. High acyl (HA) and Low acyl (LA) Gellan Gum (GG) at different ratio [75%:25% (v/v); 50%:50% (v/v), 25%:75% (v/v)], HAGG 0.75% and LAGG 2%, were mixed in order to prepare solutions to be used as formulations of GG MPs/hydrogels matrix. The GG MP/hydrogel matrix formulations were characterized by dynamic mechanical analysis (DMA), swelling behaviour and degradation rate. The toxic effect of GG MPs/hydrogel discs leachables onto the cells was investigated in vitro using a mouse lung fibroblast-like cell (L929 cells) line. Live/Dead cell viability assay was performed to assess the encapsulation efficacy; meanwhile DAPI/Phalloidin staining was performed to evaluate cell morphology. The Methacrylated Gellan Gum (GG-MA) was prepared following the protocol [1]. Mechanism reactions occurred in presence of glycidyl methacrylate by addition to a solution of LAGG at 2% (w/v). The reaction was running over 24 h at room temperature controlling the pH at 8.5 with sodium hydroxide 1 M. GG MPs size was measured using a stereo microscope by staining the MPs with Toluidine Blue-O. This method also allowed evaluating the MPs dispersion and matrix cohesion. From DMA analysis it was observed that the range of 50–500 mg/mL of incorporated MPs is the optimal concentration to reinforce GG matrices. It was demonstrated the non–cytotoxic effect of MPs/hydrogels over L929 cells. In fact, L929 cells were successfully encapsulated in all GG formulations GG MPs and remaining viable over 72 h of culturing. The resulting product from methacrylation reaction was evaluated by nuclear magnetic resonance to assess the reaction efficiency and the degree of substitution. Methacrylated Gellan gum and GG MP/hydrogel matrix are promising hydrogels to be used in tissue engineering strategies for treatment of the degenerated NP.